Effect of barrier recess on transport and electrostatic interface properties of GaN-based normally-off and normally-on metal oxide semiconductor heterostructure field effect transistors. (November 2016) - Capriotti, M.; Bahat Treidel, E.; Fleury, C.; Bethge, O.; Ostermaier, C.; Rigato, M.; Lancaster, S.L.C.; Brunner, F.; Detz, H.; Hilt, O.; Würfl, J.; Pogany, D.; et al.
Abstract: We perform a comprehensive electrical transport and physical characterization of metal oxide semiconductor heterostructure field effect transistors with ZrO2 gate dielectrics, having partially (referred here as MOS-HFET) and fully (here called true-MOS-FET) recessed GaN/AlGaN/GaN barrier, giving normally-on and normally-off behavior, respectively. The mobility of the MOS-HFETs decreases with the proximity of the Coulomb scattering centers, situated at the ZrO2 /AlGaN interface. The effect of the etching procedure and ZrO2 deposition on the formation of the interfacial charges, N int, is evaluated by X-ray Photoelectron Spectroscopy and by fitting the threshold voltage values to numerical model. For the both device types, the extracted value of N int lies within 15% around 2.8 × 10 13  cm −2, which is of the order of polarization charge, showing that our low-damage three step etching procedure does not introduce extra interface states.